Dynamic gravitational excitation of structural resonances in the hertz regime using two rotating bars - Brack Tobias; Fankhauser Jonas; Zybach Bernhard; Balabdaoui Fadoua; Kaufmann Stephan; Palmegiano Francesco; Tomasina Jean-Claude; Blunier Stefan; Scheiwiller Donat; Dual Jürg (Communications Physics, 2023)
Abstract With the planning of new ambitious gravitational wave observatories, fully controlled laboratory experiments on dynamic gravitation become more and more important. Such experiments can provide new insights in potential dynamic effects such as gravitational shielding or energy flow and might contribute to bringing light into the mystery still surrounding gravity. Here we present a laboratory-based transmitter-detector experiment using two rotating bars as transmitter and a 42 Hz, high-Q bending beam resonator as detector. Using a precise phase control to synchronize the rotating bars, a dynamic gravitational field emerges that excites the bending motion with amplitudes up to 100 nm/s or 370 pm, which is a factor of 500 above the thermal noise. The two-bar design enables the investigation of different transmitter configurations. The detector movement is measured optically, using three commercial interferometers. Acoustical, mechanical, and electrical isolation, a temperature-stable environment, and lock-in detection are central elements of the setup. The moving load response of the detector is numerically calculated based on Newton’s law of gravitation via discrete volume integration, showing excellent agreement between measurement and theory both in amplitude and phase. The near field gravitational energy transfer is 1025 times larger than the one of the propagating gravitational wave component.